Peran Guru Penggerak Terhadap Penerapan Pembelajaran Kurikulum Merdeka dalam Meningkatkan Keterampilan Belajar PAI di SDN Timbang - Rusmalawati, Eti; Syibromilisi, Syibromilisi; Wardatushobariah, Neng (Permata : Jurnal Pendidikan Agama Islam, 2024)
The implementation of Merdeka Curriculum at SDN Timbang aims to create a more flexible and student-based learning environment, but faces challenges in improving students' Islamic Religious Education learning skills. This study aims to identify the role of the Activator Teacher in implementing learning strategies that can increase engagement and Islamic Religious Education learning skills in the elementary school environment. The research method used is descriptive qualitative, with data collection techniques through observation, in-depth interviews with Master Teachers, and document analysis related to the Merdeka Curriculum policy. The research findings show that the Activating Teacher plays a role in facilitating interest-based learning, implementing collaboration between students, conducting process-based assessments, and building an inclusive learning environment to support students' emotional well-being. In addition, collaboration with parents is also proven to strengthen students' Islamic Religious Education learning skills in project-based learning. The recommendation from this study is that other elementary schools can strengthen the role of the Activator Teacher as an agent of change in improving Islamic Religious Education learning skills and student learning engagement through the Merdeka Curriculum. Keywords: Activator Teacher; Merdeka Curriculum; Learning Skills; Islamic Religious Education